Clinical and Functional Characterization of Novel INSR Variants in Two Families With Severe Insulin Resistance Syndrome - Zhou, Qiaoli; Yu, Jing; Yuan, Xuewen; Wang, Chunli; Zhu, Ziyang; Zhang, Aihua; Gu, Wei (Frontiers in Endocrinology, 2021)
Objective Defects in the insulin receptor (INSR) gene cause various severe insulin resistance conditions, including Donohue syndrome (DS), Rabson-Mendenhall syndrome (RMS) and type A insulin resistance (type A-IR). This study aimed to investigate the clinical characterization and molecular defects in three Chinese children with INSR-related insulin resistance syndrome. Methods We reviewed the clinical data of three Chinese children with INSR-related insulin resistance syndrome from two unrelated kindreds. Genetic analysis was performed using whole-exome sequencing and the effects of the novel variants were further assessed by in vitro functional assays. Results The proband with type A-IR presented with acanthosis nigricans, hypertrichosis, and euglycemia with mild insulin resistance in early childhood. His sister presented with features typical of type A-IR and was diagnosed with diabetes mellitus with severe insulin resistance at the age of 9.8 years. The proband with DS showed typical dysmorphic characteristics, severe intrauterine growth retardation, extreme insulin resistance, fasting hypoglycemia and postprandial hyperglycemia from birth. The heterozygote variants c.[3670G>A]; c.[3614C>T] were identified in both siblings with type A-IR; and c.[749_751del]; c.[3355C>T] in the patient with DS. In vitro studies showed that the novel variant c.749_751del [p.(Thr250del)] in the α-subunit, reduced expression of the mature INSR protein and severely impaired INSR function. In contrast, the novel variant c.3670G>A [p.(Val1224Met)] in the β-subunit had no effect on total protein expression and phosphorylation of INSR and Akt, suggesting that the variant p.Val1224Met appeared to be tolerated and was not responsible for the severe insulin resistance. Conclusion Our study detailed the clinical features of three patients with type A-IR and DS, and identified two novel variants in the INSR gene. Functional assays indicated the novel variant p.Thr250del was pathogenic. In contrast, the novel variant p.Val1224Met was suggested to be tolerated by our experimental data, even though bioinformatics analyses predicted the variant as deleterious.